Incentives to water conservation under scarcity: Comparing price and reward effects through stated preferences. (20th January 2020) - Garrone, Paola; Grilli, Luca; Marzano, Riccardo
Abstract: Focusing on two different European institutional contexts, a stated preference approach is adopted to elicit the willingness to save water under three alternative incentive policies: a water price increase, monetary reward, and symbolic prize. In addition, two water scarcity scenarios, a 'critical' and a 'regular' scenario, are devised to analyze how information on water scarcity moderates the effect of incentives. Empirical results show that users become sensitive to monetary incentives (while they remain insensitive to non-monetary ones) when water is scarce. Batteries of pre-tests on the sample and robustness checks on the results strengthen the reliability of our findings and partially circumvent concerns related to the use of a stated preference approach. The study adds to the literature on the efficacy of economic incentives in the water sector and the role of local factors in explaining water users' response. Highlights: Responsiveness to price, monetary and symbolic rewards is measured through stated preferences. Price and monetary rewards represent incentives in the presence of water shortages. The symbolic mechanism does not affect consumers' habits, regardless of water availability. A battery of tests strengthens the robustness of our results.